Sub-micron moulding topological mass transport regimes in angled vortex fluidic flow. Issue 11 (7th May 2021) - Alharbi, Thaar M. D.; Jellicoe, Matt; Luo, Xuan; Vimalanathan, Kasturi; Alsulami, Ibrahim K.; AL Harbi, Bediea S.; Igder, Aghil; Alrashaidi, Fayed A. J.; Chen, Xianjue; Stubbs, Keith A.; Chalker, Justin M.; Zhang, Wei; et al.
Abstract : A rapidly rotating tube in the vortex fluidic device imparts submicron topological mass transport regimes, as moulded through crystallisation, polymerisation, and 'molecular drilling'. Abstract : Shear stress in dynamic thin films, as in vortex fluidics, can be harnessed for generating non-equilibrium conditions, but the nature of the fluid flow is not understood. A rapidly rotating inclined tube in the vortex fluidic device (VFD) imparts shear stress (mechanical energy) into a thin film of liquid, depending on the physical characteristics of the liquid and rotational speed, ω, tilt angle, θ, and diameter of the tube. Through understanding that the fluid exhibits resonance behaviours from the confining boundaries of the glass surface and the meniscus that determines the liquid film thickness, we have established specific topological mass transport regimes. These topologies have been established through materials processing, as spinning top flow normal to the surface of the tube, double-helical flow across the thin film, and spicular flow, a transitional region where both effects contribute. The manifestation of mass transport patterns within the film have been observed by monitoring the mixing time, temperature profile, and film thickness against increasing rotational speed, ω . In addition, these flow patterns have unique signatures that enable the morphology of nanomaterials processed in the VFD to be predicted, for example in reversible scrolling and crumbling graphene oxide sheets. Shear-stress induced recrystallisation, crystallisation and polymerisation, at different rotational speeds, provide moulds of high-shear topologies, as 'positive' and 'negative' spicular flow behaviour. 'Molecular drilling' of holes in a thin film of polysulfone demonstrate spatial arrangement of double-helices. The grand sum of the different behavioural regimes is a general fluid flow model that accounts for all processing in the VFD at an optimal tilt angle of 45°, and provides a new concept in the fabrication of novel nanomaterials and controlling the organisation of matter.